Investigation of crack propagation in single optical fiber composite with thermal influence by finite element method - Ahanchian Mohammad; Arzumanyan Hovhannes; Verlinski Sergey (Fracture and Structural Integrity)
Two parallel comparative ‘Conventional Method and Computer Simulation using ANSYS software’ for prediction of crack growth and its behavior in optical fiber are studied and presented in this work. Corresponding finite element analysis was performed to determine the evolution of stress and strain states. The method is developed and combined with the modified J-integral theory to deal with this problem. The effects of crack length, temperature and mechanical forces are investigated by Finite Element Method in the cracked body. The conditions where the Mode I stress intensity factor motivate fracture occurrence is investigated and variations of the different cases are discussed. The most deleterious situation is found to be that wherein the entire model reaches rupture at some stage. The accuracy of the method is investigated through comparison of numerical results with computerized simulation using commercial ANSYS software.